The all-ukrainian council of churches and religious organizations. Over twenty years of operation: achievements and prospects - Владиченко, Л. (Київський національний університет імені Тараса Шевченка, 2019)
This article reviews the specificity of the institutional area of interreligious and interconfessional relations in Ukraine. It highlights the preconditions for the emergence of one of the interreligious associations of Ukraine – the All-Ukrainian Council of Churches and Religious Organizations. The structure and the statutory documents of the AUCCRO are reviewed in the article. The author investigates the specifics of the activity and peculiarities of the organizational structure of the Council. The Council's cooperation with state institutions is analyzed and the problematic aspects of the interconfessional and state-confessional spheres are identified.Two periods in the existence of the AUCCRO are highlighted in the article: from 1996 to 2004 and from 2005 to the present. Particular attention is given to the prerequisites and the possibility of the emergence of the AUCCRO in correlation to the cooperation with the State body of Ukraine for religious affairs in the context of the current religious situation and interreligious/interconfessional relations at the beginning of Ukraine's independence. The formation of the AUCCRO under the central executive authority was prompted by the need to resolve property conflicts among religious organizations. The AUCCRO facilitated the dialogue between the authorities and religious organizations and involved representatives of the religious community in solving the problematic issues of the interconfessional state-religious complex at that time.The article draws attention to the change of the organizational form of the AUCCRO after the political changes in the country in 2004 and the reduction of the status of the State body of Ukraine for religious affairs. The AUCCRO has been acquiring a new format of activity, which is specified in the Regulation on the AUCCRO, since 2005. Attention is drawn to some of the inaccuracies of the statistical nature and internal organization of the AUCCRO, which is criticized by other religious communities.The practical activities of the AUCCRO and the organizational mechanism of its activity are analyzed. The author emphasizes on the topical issues for the religious community that AUCCRO raises in its appeals to the government officials. The AUCCRO's mechanism of the cooperation with the state authorities through the formation and further activity of the advisory bodies of the Ministry of Education and Science of Ukraine, the Ministry of Defense of Ukraine, the Ministry of Health of Ukraine, the Ministry of Foreign Affairs, and the penitentiary system is shown.

Розглянуто специфіку інституційної сфери міжрелігійних та міжконфесійних відносин в Україні. Висвітлено передумови виникнення одного з міжрелігійних об'єднань в Україні – Всеукраїнської ради церков і релігійних організацій. Здійснено огляд структури та статутних документів ВРЦіРО. Досліджено специфіку діяльності та особливості організаційної структури цієї Ради. Проаналізовано співпрацю Ради з державними установами та виокремлено проблемні аспекти міжконфесійної та державно-конфесійної сфер.
Всеукраїнська рада церков і релігійних організацій – понад двадцять років діяльності: здобутки та перспективи
Keywords: the All-Ukrainian Council of Churches and Religious Organizations; inter-religious associations; inter-religious and inter-confessional relations; religious organizations; state-confessional relations; Всеукраїнська рада церков і релігійних організацій; міжрелігійні об'єднання; міжрелігійні та міжконфесійні відносини; релігійні організації; державно-конфесійні відносини